Progress in NMR-based metabolomics of Catharanthus roseus - Qifang PAN,Jingya ZHAO,Yuliang WANG,Kexuan TANG (Frontiers of Agricultural Science and Engineering, 2015)
Metabolomics has been rapidly developed as an important field in plant sciences and natural products chemistry. As the only natural source for a diversity of monoterpenoid indole alkaloids (MIAs), especially the low-abundance antitumor agents vinblastine and vincristine, Catharanthus roseus is highly valued and has been studied extensively as a model for medicinal plants improvement. Due to multistep enzymatic biosynthesis and complex regulation, genetic modification in the MIA pathway has resulted in complicated changes of both secondary and primary metabolism in C. roseus, affecting not only the MIA pathway but also other pathways. Research at the metabolic level is necessary to increase knowledge on the genetic regulation of the whole metabolic network connected to MIA biosynthesis. Nuclear magnetic resonance (NMR) is a very suitable and powerful complementary technique for the identification and quantification of metabolites in the plant matrix. NMR-based metabolomics has been used in studies of C. roseus for pathway elucidation, understanding stress responses, classification among different cultivars, safety and quality controls of transgenic plants, cross talk between pathways, and diversion of carbon fluxes, with the aim of fully unravelling MIA biosynthesis, its regulation and the function of the alkaloids in the plant from a systems biology point of view.